Dexterous Undersea Interventions with Far Distance Onshore Supervision: the DexROV Project. Issue 23 (2016) - Gancet, Jeremi; Weiss, Peter; Antonelli, Gianluca; Pfingsthorn, Max Folkert; Calinon, Sylvain; Turetta, Alessio; Walen, Cees; Urbina, Diego; Govindaraj, Shashank; Letier, Pierre; Martinez, Xavier; Salini, Joseph; et al.
Abstract: The operation of a ROV requires significant off-shore dedicated manpower to handle and operate the robotic platform. In order to reduce the burden of operations, DexROV proposes to work out more cost effective and time efficient ROV operations, where manned support is in a large extent delocalized onshore (i.e. from a ROV control center), possibly at a large distance from the actual operations, relying on satellite communications. The proposed scheme makes provision for advanced dexterous manipulation capabilities, exploiting human expertise from a remote location when deemed useful. The outcomes of the project will be integrated and evaluated in a series of tests and evaluation campaigns, culminating with a realistic deep sea (1, 300 meters) trial. After one year, the project specified the system architecture of the system and carried out preliminary technological trade-offs for the subsystems.